The first pediatric case of leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) from Turkey - Çavuşoğlu, Dilek; Olgaç-Dündar, Nihal; Öztekin, Özgür; Özdemir, Taha Reşid; Arıcan, Pınar; Gençpınar, Pınar (The Turkish Journal of Pediatrics, 2018)
Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) is defined as an autosomal recessive inheritance disorder characterized by slowly progressive cerebellar, pyramidal and dorsal column dysfunction. The diagnosis is based on specific magnetic resonance imaging abnormalities (MRI) in the cerebral and cerebellar white matter and selective involvement of white matter tracts in the brain stem and spinal cord. LBSL is caused by mutations in the DARS2 gene which encodes the mitochondrial aspartyl-tRNA synthetase. Herein, we report the first pediatric case from Turkey with a typical MRI course of LBSL associated with a compound heterozygous mutation in DARS2 gene.